Monetary policy transmission mechanism and growth of the manufacturing sectors in Libya and Nigeria - Omolade, Adeleke; Ngalawa, Harold (Journal of Entrepreneurship, Business and Economics, 2016)
The study examines the role of exchange rate regimes in determining the nature of relationship be-tween monetary policy transmission mechanisms and manufacturing output growth in oil producing economies in Africa. Libya and Nigeria were used in the study because of the different exchange rate regimes practice in both oil exporting countries. Nigeria as a net oil exporter practices flexible ex-change rate while Libya as a net oil exporter practices fixed exchange rate system. The study employs structural variance decomposition approach (SVAR). It was found out from the study that exchange rate regime has some influences on the monetary policy transmission mechanism and its effectiveness on the manufacturing output growth in the two oil exporting countries. Oil price shocks affect the monetary policy instrument of both countries greatly. While monetary policy instrument appears to be ineffective in promoting output growth of the manufacturing sector in Libya that practices fixed ex-change rate, the reverse is the case in Nigeria. Flexible exchange rate appears to create enabling envi-ronment for monetary policy instrument to influence manufacturing output growth positively in the face of oil price shock. Research paper Reference to this paper should be made as follows: Omolade, A. Ngalawa, H. (2017). “Monetary policy transmission mechanism and growth of the manufacturing sectors in Libya and Nigeria: Does exchange rate regime matter?”, Journal of Entrepreneurship, Business and Economics, Vol. 5, No. 1, pp. 67–107.